(untitled) (Hekima Review, 2005)
For millennia, humans have inhabited the earth and have relied on it for sustenance as well as for the gratification of humans’ insatiable appetite for materialism. Initially, humans loved the environment and viewed it as a major partner in their earthly journey. In other words, mutual benefit marked the relationship existing between humans and the natural habitat. They got their livelihood from their surrounding and in return, gave back what the environment needed for its continuity, peace. Cultures and tribes around the world respected the environment from which they sustained their livelihood. These tribes some of which could be found in Africa worshipped the physical environment in which they lived. The mountains, oceans, seas, rivers, forests, valleys, plains, basins, deserts, seasons, and the skies represented not merely exploitable components of the earth, but also sacred sanctuaries which deserved respect from humans.